Professional problems of teachers - Stinnet, T. M.; Hugget, Albert J. (New York : Macmillan Publishing Company, 1965)
The first edition of this text was a pioneer in its field. Its purpose was to provide basic information, for college students shortly to enter teaching and for recent graduates who had begun a teaching career, on a cluster of problems with which members of the teaching profession must deal daily as practitioners and as effective members of their professional organizations. The wide use of this volume and several other textbooks subsequently published in the field attest to the interest in providing such orientation. The text, therefore, was an effort to contribute to the growing movement to professionalize teaching by developing competence in the individual to function as a professional person as well as a teacher.
I. Education in America -- II. The Teacher as a member of a profession -- III. Professional personnel policies and working conditions -- IV. Developing responsibilities and rights of teachers -- V. Safeguarding teaching as a profession.
Includes bibliographical references and index.
Keywords: TEACHING